The RANKL/OPG system is activated in inflammatory bowel disease and relates to the state of bone loss. Issue 4 (7th March 2005) - Moschen, A R; Kaser, A; Enrich, B; Ludwiczek, O; Gabriel, M; Obrist, P; Wolf, A M; Tilg, H
Abstract : Background and aims: A substantial proportion of patients with inflammatory bowel disease (IBD) develops osteopenia and osteoporosis in the course of disease. Recent data from a mouse model of colitis suggest that the receptor activator of nuclear factor kappa B (RANKL)/osteoprotegerin (OPG) system may be responsible for bone loss. Methods: We investigated the activation state of the RANKL/OPG system and its association with bone loss in human IBD. Plasma levels of OPG and RANKL were correlated with bone mineral density and current IBD therapy. Colonic secretion of OPG and RANKL and cell types responsible for such secretion were determined. Results: OPG plasma levels were elevated 2.4-fold in Crohn's disease (CD) and 1.9-fold in ulcerative colitis (UC) whereas soluble RANKL (sRANKL) levels were not significantly different in IBD patients compared with healthy controls. High levels of OPG were released from colonic explant cultures (CEC) derived from inflamed IBD specimens, and colonic macrophages and dendritic cells costained for OPG. sRANKL levels from CEC were low both in IBD patients and healthy controls. Interestingly, increased expression of RANKL was mainly confined to cells in the lamina muscularis. A significant negative correlation was found between OPG plasma levels and femoral neck/lumbar spine bone mineral density. Conclusions: We have demonstrated that IBD is associated with alterations in the RANKL/OPG system. Applying results from a murine model of colitis associated bone loss, the constellation of OPG and sRANKL regulation observed in our study raises the possibility that RANKL/OPG may contribute to the development of bone loss in IBD.